2005
DOI: 10.1007/s00417-004-1085-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal detachment in south India—presentation and treatment outcomes

Abstract: The profile of retinal detachments in a tertiary eye care centre in south India includes many paediatric cases, late presentations and macula-off detachments, commonly related to cataract surgery. Despite complex pathology, two thirds of eyes regain useful vision after one or more surgical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
1
22
6
1
Order By: Relevance
“…Reflecting on the diverse nature of the Indian population and variable regional services, the current study was conducted to investigate patterns and attributes of RD in Northern India. We found a higher number of pseudophakic patients, macula off detachments and bilateral RDs than other developing nations like Kenya (Yorston et al, 2002), South Africa (Peters, 1995), Nepal (Malla et al, 2009), Pakistan (Jamil et al, 2012), south India (Jalali et al, 2005) and other developed nations (Mitry et al, 2010). Discussing reasons and implications for the same is beyond the scope of this study (unpublished data).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Reflecting on the diverse nature of the Indian population and variable regional services, the current study was conducted to investigate patterns and attributes of RD in Northern India. We found a higher number of pseudophakic patients, macula off detachments and bilateral RDs than other developing nations like Kenya (Yorston et al, 2002), South Africa (Peters, 1995), Nepal (Malla et al, 2009), Pakistan (Jamil et al, 2012), south India (Jalali et al, 2005) and other developed nations (Mitry et al, 2010). Discussing reasons and implications for the same is beyond the scope of this study (unpublished data).…”
Section: Discussionmentioning
confidence: 48%
“…Although a notable study regarding patterns of RD from southern India has been done (Jalali et al, 2005), there is a void of information from Northern India. Reflecting on the diverse nature of the Indian population and variable regional services, the current study was conducted to investigate patterns and attributes of RD in Northern India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical outcomes were comparable to a large study with various grades of PVR (71%) in normal eyes with RRD done at our center. 7 As most eyes with albinism may not have normal visual acuity due to nystagmus and foveal hypoplasia, 8 comparison with visual outcomes with non-albinotic cases would be irrelevant. At the last follow-up, all eyes showed improvement or stabilization of vision.…”
Section: Discussionmentioning
confidence: 99%
“…The Ophthalmic Procedure Assessment of the American Academy of Ophthalmology recommended that fovea-on RD should be operated on as soon as possible, preferably within 24 hours. 12 Another problem is that more than two thirds of new patients (68%, 4 75%, 13 and 86.8% 14 ) according to the previous reports already have macula-off RD when they visited the outpatient clinic of the operating facilities. Quinn et al 15 reported that avoidable delays in presentation of patients with RD to a tertiary referral center caused by inadequate referral pathway and inadequate public awareness of ophthalmic emergencies should be eliminated.…”
mentioning
confidence: 98%